2017
DOI: 10.1158/1535-7163.mct-16-0589
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Pharmacological Characterization of JNJ-42756493 (Erdafitinib), a Functionally Selective Small-Molecule FGFR Family Inhibitor

Abstract: Fibroblast growth factor (FGF) signaling plays critical roles in key biological processes ranging from embryogenesis to wound healing and has strong links to several hallmarks of cancer. Genetic alterations in FGF receptor (FGFR) family members are associated with increased tumor growth, metastasis, angiogenesis, and decreased survival. JNJ-42756493, erdafitinib, is an orally active small molecule with potent tyrosine kinase inhibitory activity against all four FGFR family members and selectivity versus other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
200
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(219 citation statements)
references
References 32 publications
3
200
1
1
Order By: Relevance
“…An interim analysis of data from this study indicated that NVP-BGJ398 has impressive antitumour activity, with a disease-control rate of 82%, and a manageable safety profile 106 . Erdafitinib is another orally active, pan-FGFR inhibitor 107 , and is being investigated in clinical trials. In a phase I dose-escalation study (NCT01703481), erdafitinib had a manageable safety profile at doses associated with clinical responses; among 23 response-evaluable patients with solid tumours harbouring FGFR-pathway alterations, four patients had a confirmed response to treatment with erdafitinib, one had an unconfirmed partial response, and 16 had stable disease 108 .…”
Section: Emerging Molecularly-directed Therapiesmentioning
confidence: 99%
“…An interim analysis of data from this study indicated that NVP-BGJ398 has impressive antitumour activity, with a disease-control rate of 82%, and a manageable safety profile 106 . Erdafitinib is another orally active, pan-FGFR inhibitor 107 , and is being investigated in clinical trials. In a phase I dose-escalation study (NCT01703481), erdafitinib had a manageable safety profile at doses associated with clinical responses; among 23 response-evaluable patients with solid tumours harbouring FGFR-pathway alterations, four patients had a confirmed response to treatment with erdafitinib, one had an unconfirmed partial response, and 16 had stable disease 108 .…”
Section: Emerging Molecularly-directed Therapiesmentioning
confidence: 99%
“…Advanced stage solid malignancies, including iCCA are included into several selective and non‐selective FGFR inhibitors for early phase clinical trials . Pan‐FGFR inhibitors as NVP‐BGJ398 and erdafitinib showed potential as well manageable safety profiles . NVP‐BGJ398 showed impressive results by a disease control rate of 82% and tumour‐activity results of erdafitinib from the ongoing phase II trial (NCT02699606) will be presented soon .…”
Section: Modulating Each Single Cell Compartment For Therapeutic Gainmentioning
confidence: 99%
“…Female immunocompromised NMRI nu/nu mice from Janvier were injected s.c. with 3 × 10 6 NCI-H716 human colon cancer cells, randomized (n = 8/group) on day 22 (average tumor volume 63-99 mm 3 ) and treated for 17 days with vehicle or rogaratinib (35,50 or 65 mg/kg, BID, p.o.). Female NMRI nu/nu nude mice from Janvier were injected s.c. with 2 × 10 6 DMS-114 human SCLC cells, randomized (n = 8/group) on day 13, and treated for 10 days with vehicle, rogaratinib, chemotherapy or combinations.…”
Section: Antitumor Efficacy In Cell Line and Patient-derived Xenografmentioning
confidence: 99%
“…(c) Expression of p-FGFR2, p-ERK, total ERK and actin in NCI-H716 tumor tissue after rogaratinib treatment. After a drug-free observation period of 10 days, mice of the three rogaratinib-dose groups (35,50 or 65 mg/kg) in (a) received a single respective dose of rogaratinib or vehicle. Plasma and tumors were collected 1, 2, 5 or 24 h after treatment for PK/PD analysis and phosphorylation of FGFR2 and ERK1/2 was determined by Western blotting.…”
Section: Antitumor Activity Of Rogaratinib In Various Fgfr2 Overexprementioning
confidence: 99%